ECOLOGICAL POLICY OF EU COUNTRIES REGARDING THE REGULATION OF PUBLIC RELATIONS IN THE FIELD OF MAINTAINING ENVIRONMENTAL SAFETY - Беспалова, Ольга В'ячеславівна (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2020)
Introduction. The article is devoted to the analysis of the environmental policy of the EU countries on the regulation of public relations in the field of environmental safety. The article clarifies the legislative definition of environmental safety in Ukraine. It was found that the indicator that comprehensively reflects various aspects of the environment, the sustainability of ecological systems, as well as the effectiveness of state policy in the field of ecology is the index of environmental efficiency. The index of ecological efficiency in the context of the countries of the European Union is analyzed. The author calculates the dynamics of changes in the environmental performance index for EU countries. The division of EU countries by regions has been carried out.Summary of the main research results. The environmental legislation of the EU countries, in particular, Denmark, Slovakia, France and Malta, which have the highest indicators of the environmental efficiency index for 2018 in their region, is analyzed. The place of Ukraine in the specified rating is defined. It is determined that the environmental efficiency index for 2020 is calculated according to the new methodology, so it can no longer be used in retrospect.It is found that maintaining environmental safety is a complex concept that encompasses a wide range of measures, procedures and practices to maintain environmental safety and human security at the proper level of their existence, in order to protect them from anthropogenic impacts and natural changes.Conclusions. It is concluded that for the most part the structure and content of environmental legislation of the EU is similar to the Ukrainian, both in terms of specialization of laws and government agencies that ensure compliance with regulations. However, the low efficiency of our public services is still linked to the Soviet legacy (as in Slovakia). The need for a more detailed analysis and outline of prospects for the implementation of the Danish experience in Ukraine on the regulation of land relations, rules for the use of fertilizers, implementation of programs for the use of nitrates, opportunities for benefits for farmers. It is determined that the main leitmotif of EU environmental policies is the greening of the economy and large-scale use of renewable energy sources. Emphasis is placed on the urgent need for a comprehensive policy of environmental education of Ukrainian citizens, starting from school age.